Accompanying evidence of legislation at the fundamentalists (Journal of the College of Basic Education, 2023)
Praise be to God, who illuminated the universe with the light of Islam, and revealed the Qur’an to the best of mankind, the book that falsehood does not come to from before it or from behind it, the revelation of the All-Wise, the All-Knowing, the eternal message, free from errors and illusions, characterized by harmony and harmony.And prayers and peace be upon the best of creation, the teacher of humanity, our master Muhammad, may God bless him and grant him peace, and his family and companions who believed in him and followed his clear guidance, intending thereby to please the Lord of the Worlds.And after:The Islamic Sharia came comprehensive to all aspects of man in his life and after his death, in his acts of worship and transactions, and in all his individual and collective affairs. The science of the principles of jurisprudence is of great importance in Islamic Sharia because it is the science that is the basis for ijtihad and the deduction of Sharia rulings from the sources and legal evidence textual and ijtihad. Accurate to the principles of diligence, and the pillar in understanding the Sharia, so it was indispensable for any jurist or agreed upon, scholar or learner, to train him on how to jurisprudence, and to introduce him to the methods of deduction, and to realize the interests and buildings on which the Sharia is based, and in this research I touched on an important topic One of his topics, except that it is companionship evidence from the evidence of the legislation of the fundamentalists.I divided my research into an introduction, five topics and a conclusion:The first topic: I dealt with the meaning of companionship linguistically and idiomatically, and its conditions and pillars.Accompanying language: Asking for companionship, i.e. accompaniment and not separating, and accompanies the thing to be necessary, and it is said that the thing asked him to make it in his company, and so-and-so invited him to the company.